Sikap Mahasiswa PPKn Universitas Lampung Terhadap Ujaran Kebencian (Hate Speech) Di Sosial Media Tahun 2019 - Annisa Suciati; Yunisca Nurmalisa; Rohman Rohman (FKIP Unila, 2019)
The purpose of this study is to explain how the attitude of the PPKn students to the case of hate speech. The method used is descriptive. The results of the study showed the views of students (cognition indicators) of 14 respondents or 51.9% of students had the view that the prevalence of cases of hate speech was caused by the presence of social media. Feelings of students (affection indicators) shaowed that 15 respondents or 55.6% of students felt that the case of hate speech made by social users can have a bad influence on other social media users. While the response of students (conative indicators) from 14 respondents or 51.9% of students was less amenable to the sanctions given by the perpetrators of cases of hate speech in social media. Tujuan penelitian ini adalah untuk menjelaskan bagaimana sikap mahasiswa PPKn terhadap kasus ujaran Kebencian (Hate speech). Metode yang digunakan adalah deskriptif. Hasil penelitian, menunjukkan pandangan mahasiswa (indikator kognisi) dari 14 responden atau 51,9% mahasiswa memiliki pandangan bahwa maraknya kasus ujaran kebencian salah satunya disebabkan oleh kehadiran Sosial Media. Perasaan mahasiswa (indikator afeksi) dari 15 responden atau 55,6% mahasiswa merasa bahwa bahwa kasus ujaran kebencian yang dilakukan oleh pengguna sosial dapat memberikan pengaruh buruk bagi pengguna Sosial Media lainnya. Sedangkan respon mahasiswa (indikator konasi) dari 14 responden atau 51,9% mahasiswa kurang setuju terhadap adanya sanksi yang diberikan oleh pelaku kasus ujaran kebencian di Sosial Media. Kata kunci : Sikap, Ujaran Kebencian, Sosial Media.